The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/07399332.2017.1338705
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mammography adoption among iranian women: What are the differences in the cognitive factors by the stages of test adoption?

Abstract: Our aim in this cross-sectional study was to investigate the predictors of the stages of change in mammography adoption (MA) based on Health Belief Model among Iranian women. Through multistage cluster sampling, we recruited and interviewed 1131 women older than 40. After statistical adjustment for other risk factors, perceived barriers (OR D 0.84, 95% CI D .81-.87) and benefits (OR D 1.17, 95% CI D 1.11-1.24) were significant predictors for MA. Majority of the women were in the pre-contemplation and contempla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…In the current study, I do not do mammograms because of my fear of breast cancer, mammography costs is a lot, and not knowing about how to get mammography test were three main cons for mammography among women. Similar to our findings, results of Shirzadi's study this finding is confirmed (Shirzadi et al, 2017). Previous studies have reported a various range of cons to seeking for mammography screening tests including the lack of knowledge (Jones et al, 2014), Fear (Fayanju et al;Abu-Helalah et al, 2015), costs of the test (Watson-Johnson et al, 2011;Abu-Helalah et al, 2015), time-consuming mammography test (Sarma, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, I do not do mammograms because of my fear of breast cancer, mammography costs is a lot, and not knowing about how to get mammography test were three main cons for mammography among women. Similar to our findings, results of Shirzadi's study this finding is confirmed (Shirzadi et al, 2017). Previous studies have reported a various range of cons to seeking for mammography screening tests including the lack of knowledge (Jones et al, 2014), Fear (Fayanju et al;Abu-Helalah et al, 2015), costs of the test (Watson-Johnson et al, 2011;Abu-Helalah et al, 2015), time-consuming mammography test (Sarma, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…One of the issues that may affect women's performance and perception is the existence of such factors as creating facilities such as mammography centers, increasing knowledge and attitude towards mammography, and appropriate coverage for eligible women (Shirzadi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because they perceived mammogram to be painful, embarrassing (Alexandraki and Mooradian, 2010) and the fear of radiation dose (Cam and Gumus, 2009). These facts are further supported by other studies which discovered that women who are in the action or maintenance stage have higher perceived susceptibility of breast cancer as compared to other mammography behavior adoption stages (Lindamer et al, 2006;Allahverdipour et al, 2011;Shirzadi et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, if individuals are not engaged in the problem-focused coping, they are likely to avoid stressful situations or deny the existence of a stressful situation and, instead, look on the brighter side of life. 25) Body image, obvious changes in the body shape after mastectomy, and unpleasant feelings about the size and shape of one's breasts, new roles as an 'unattractive' women, or interference in sexual relationships can have negative impacts on woman's decision to undergo mammography screening. 26) As a result, public health professionals and healthcare providers should provide coherent information about the benefits of mammography and the importance of early diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%